(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Myofascial trigger points are common in upper trapezius which can occur at any age due to the spasm of upper trapezius, causing difficulty in sitting in the flexed posture and can eventually lead to chronic cervical pain, disability and diminished quality of life. Dynamic tape, a new approach applied in a shortened position, has a good leverage to maximize load absorption involving a degree of stretch that contributes to the lightening of muscular load. This is the first case study where dynamic tape has been used to relieve symptoms in upper trapezius pain syndrome.